Environmental and Economic Benefits of Selecting Beef Cattle for Feed Efficiency - Nicolas DiLorenzo; G. Cliff Lamb (EDIS)
Selecting for feed efficiency based on residual food intake can significantly impact the amount of nutrients consumed and excreted per cow without compromising animal performance. Fresh manure output and excretions of phosphorous and nitrogen could be reduced by 29%, while methane emissions can be reduced by as much as 28% when selecting more feed-efficient animals. This 4-page fact sheet was written by Nicolas DiLorenzo and G. Cliff Lamb, and published by the UF Department of Animal Science, February 2012.